The Level of satisfaction of school principals to the educational supervisors services In public schools in Aqaba-Jordan - Abu Hamde, Elham Naif (Journal of Educational and Psychological Sciences, 2022)
The present study aimed at identifying the level of satisfaction of school principals to the educational supervisors services in public schools in the city of Aqaba, Jordan. The sample population consisted of the schools principals (60) individuals, divided into (14) males and (56) females. To achieve the objectives of the study, the researcher developed a questionnaire consisting of (35) items. The results of study indicated that the level of satisfaction of school principals the educational supervisors services was moderate, and the results indicated that there were no statistically significant differences between the averages in the sample’s views due to gender.